pH-Responsive Bacterial Nanocellulose Smart Labels Derived from Acid Whey for Estimating Beef Mince Quality Alterations During Storage - Dylan Zhe Liu; Sabeen Hassan; Benjamin M. Long; Alan Labas; Jayendra K. Amamcharla; Michelle J. Y. Yoo; Xiaojie Hu; David C. Bean (Foods)
This study develops a pH-responsive label by incorporating anthocyanin from Clitoria ternatea into a bacterial nanocellulose (BNC) film derived from acid whey fermentation. The labels were designed to display two distinct colors—pink and purple—by adjusting the pH of anthocyanin and were integrated into beef mince packaging to monitor quality changes over a 15-day storage period at 4 °C. Color variations were assessed using a chroma meter and visual inspection, with both label types exhibiting a shift to blue in response to a deterioration in freshness. Significant differences (p < 0.05) in total color difference (∆E) were observed across data collection days. The pink label showed an ∆E of 14.19 between day 0 and day 8, increasing to 27.39 by day 15. The purple label exhibited an ∆E of 12.94 by day 8 and 27.86 by day 15. A Total Volatile Basic Nitrogen (TVBN) analysis and microbial evaluations confirmed a degradation in the quality of the beef mince, with strong correlations between ∆E and ∆TVBN (r = 0.956 for pink, r = 0.993 for purple). Additionally, good correlations were recorded between label total color differences and coliform counts (r = 0.933 for pink, r = 0.875 for purple), as well as Total Plate Counts (TPCs) (r = 0.982 for pink, r = 0.950 for purple). These results highlight the potential of acid whey-derived nanocellulose films as real-time quality indicators for intelligent food packaging systems.